Guinness worl records 2020 Annual edition (Pakistan : Guinness World Records Limited, Paramount Books (Pvt.) Ltd., 2020)
Guinness World Records 2020 is a vibrant, fact-packed annual showcasing the latest and most astonishing world records. It features extraordinary human feats, incredible animals, cutting-edge technology, and natural wonders, all presented through engaging chapters, striking photos, and special (3z(BSnapshot(3y (Bpages. Designed to inspire curiosity, it offers a global tour of remarkable achievements from adventurers, artists, athletes, and innovators.s
Keywords: General Works - Reference Book